If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 2) + 5x = 8 Reorder the terms: -2(2 + x) + 5x = 8 (2 * -2 + x * -2) + 5x = 8 (-4 + -2x) + 5x = 8 Combine like terms: -2x + 5x = 3x -4 + 3x = 8 Solving -4 + 3x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3x = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 8 + 4 3x = 8 + 4 Combine like terms: 8 + 4 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 4x+2-2x=3x-8 | | 2*315/7x=13x-9 | | 128*2/8x=8 | | 0=-6-66 | | 2n^2-12n+10/2n^2-7n-15 | | y=3x^2+12x-6 | | 15x-8/4=3x+2,54 | | 735/7x=-35 | | (x+-2)(x+-2)=3 | | 7d+9=3d+37 | | -2t-5=3 | | 291-x=141 | | n^2+n-24=0 | | 4/5+4x=0.2 | | 1=4c-3 | | 0.6x-0.5(40+x)=-0.4(40) | | 265=85-y | | -v+167=108 | | 2e-9=-6.6 | | 258-7x=38x-23 | | 6x^2+9=21x | | 2/5+6x=0.2 | | 7p=60.2 | | 5/4+5x=0.5 | | -1.2+w/3=-108 | | 15-3x=2.43 | | f(x)=5-x^5 | | (y+7)+(y-3)+(y-3)-(y+3)= | | 4/5+3x=0.4 | | (m)+(2)+(9)-(10m)= | | f(x)=-2400+15x^2 | | 5x+9=x-8 |